A matching-game-based satisfactory spectrum leasing for cognitive-radio-empowered 5G. (2019) - Handouf, Sara; Bouassam, Hamid; Sabir, Essaid; Sadik, Mohamed
Cognitive radio allows flexible self-organising solution for spectrum scarcity management. It can be used to improve spectrum utilisation while protecting larger range of coexisting users. In this article, we present a new spectrum leasing solution using the matching theory. Based on this Nobel Prize winning framework, a novel distributed scheme, for joint resource management and business side, is built. Yet, we exhibit a new scheme, whereby multiple primary users (PUs) and secondary users (SUs) interact with one another to select their best possible partner optimising their own benefits. To efficiently use available spectrum, each SU seeks to be allocated a channel with sufficient bandwidth and low cost. Numerical investigations illustrate how stable the matching scheme and how it outperforms standard resource allocation. It is also compared with flat rate multiple access scheme via implementing the two schedulers in terms of network size, SUs' QoS demand and bandwidth fee.